Epistemic beliefs and knowledge creation among upper-secondary students in transdisciplinary education for sustainable development - Grice, Marie (Nordidactica: Journal of Humanities and Social Science Education, 2014)
This study examines the epistemic beliefs of upper-secondary school students (n=208) involved in a transdisciplinary project regarding sustainable development. Specifically the dimensions of knowle ...